Depressive symptoms and antidepressant use in a random community sample of ethnically diverse, urban elder persons - Grunebaum, Michael F.; Oquendo, Maria A.; Manly, Jennifer J. (Journal of affective disorders, 2008)
There are limited data on depressive symptoms and antidepressant use in ethnically diverse, urban elderly. Analysis of depressive symptom and antidepressant use data from an epidemiological survey of dementia in an ethnically diverse, urban, elderly community. 21.5% ( N = 566) reported clinically significant depressive symptoms. Severity was inversely associated with socioeconomic status. 7.5% ( N = 194) reported antidepressant medication use. Multiple logistic regression analysis adjusting for severity and other covariates showed that men and African Americans had nearly half the odds of using antidepressants. Antidepressant use was more frequent among Hispanics, those with more severe depression and more medical illness. Combined sample; CES-D not validated in Hispanics and inner-city African Americans; depressive symptoms assessed at one time-point; lack of complete income data; geographically restricted. In this elder sample, taking into account depressive symptom severity and other confounds, antidepressant use is nearly half as likely among men and African Americans.